The complexity of diagnosing sarcoma in a timely manner: perspectives of health professionals, patients, and carers in Australia - Rhys Weaver; Moira O'Connor; Richard Carey Smith; Georgia KB Halkett (BMC, 2020)
Abstract Background Prolonged diagnosis intervals occur more often in rare cancers, such as sarcoma. Patients with a delayed diagnosis may require more radical surgery and have a reduced chance of survival. Previous research has focused on quantifying the time taken to achieve a diagnosis without exploring the reasons for potential delays. The aim of this study was to explore patients', carers', and health professionals' perceived barriers to timely diagnosis and referral for treatment for sarcoma. Methods Semi-structured interviews were conducted with: health professionals working with sarcoma (n = 21); patients who have been diagnosed with sarcoma (n = 22); and carers of patients diagnosed with sarcoma (n = 17). Interview transcripts were analysed using thematic analysis. Results Four overarching themes were identified: patient perception of symptoms, difficulties of diagnosis, lack of experience, and availability of health services. Diagnosis was prolonged by the limited availability of health services, lack of prompt referrals to a sarcoma specialist centre, and diagnostic challenges. Intervals also occurred when patients underestimated the severity of their symptoms and did not seek prompt medical consultation. Conclusions Patients with a potential sarcoma need to be promptly referred to a sarcoma specialist centre and additional diagnosis pathways need to be developed to reduce the rate of patients being referred to wrong specialists. Sarcoma education must be embedded in medical courses and professional development curricula. A public health approach should be taken to improve sarcoma knowledge and health seeking behaviours in the community.